Analysis of Household Lighting Fuel Choice in Rwanda, Africa: Using the Multinomial Logit Model - Niyonshuti, Emmanuel (Journal of Business and Social Sciences Research, 2021)
This paper seeks to identify the determining control factors that influence the fuel energy choice for lighting purposes in Rwanda by applying the Multinomial Logit Regression to the national representative survey at household level data. The study revealed that the households with higher income adopt the use the cleaner and modern fuel energy sources, confirming the hypothesis for the energy ladder. Not only household income exerting impact on the fuel energy choice for lighting, but also the other fuel choices that are the significant determining variables in Rwanda are the number of the rooms occupied by household, type of dwelling for household, age of the household head, whether the household head has the formal education, the household size, type of the habitat for the household and the location of the household. This paper suggests deployment and utilisation of solar potential for supplying the cleaner and modern fuel energy for lighting purposes in the remote area of Rwanda (Africa) which may be replicated in other developing countries in the world.